Penerapan Teknik Focus Group Discussion Dalam Perencanaan Karir Santriwan Di SMA IT Izzatuna Palembang - Yudhi Permana Kusma Dewi; Suryati suryati; Neni Noviza (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "the application of focus group discussion techniques in the career planning of students at SMA IT Izzatuna Palembang". This study aims to see how the career planning of students after graduating from school through focus group discussion techniques. This type of research is field research using a qualitative approach with descriptive methods. Data collection techniques using observation, interviews, and documentation. The research subjects included 4 people, namely 3 students and 1 principal at SMA IT Izzatuna. According to Sugiyono there are three types of data analysis, namely, data reduction, data display and conclusion or data verification. The results of the study were obtained from observations and interviews 1) a description of the career plans of the students after graduating from SMA IT Izzatuna Palembang, that is, there are students who have not yet decided on their career plans because they are afraid of choosing the wrong path after they graduate from school later. 2) the application of the focus group discussion technique in the careers of the students that as a result of the application of the FGD technique to the students, in the end there is an increase before and after the FGD technique is given to overcome problems related to the career selection of students which helps to understand themselves, the environment, values the value of problem solving and decision-making ability is the initial foundation for the formation of career maturity, namely the readiness of students to make career decisions. KEYWORDS: Focus Group Discussion Techniques, Career Planning, Students